Understanding the Egyptian Spring - Kazi, Khurram J. (ADA University, 2013)
Rapid and spontaneous uprisings in the Middle East and North Africa (MENA) surprised the world when they overthrew decades old regimes, considered to be exceedingly stable. The research aims at critically addressing two key questions: Why did the revolution take place? And how did the revolution succeed? This is an endeavor aimed at broadening the perspective by uncovering some of the root causes of the uprising in Egypt. The research reached to a conclusion that a number of factors have contributed towards the overthrow of dictatorial regime in Egypt including: daily humiliation and abuse at the hands of police and other internal security forces; massive corruption in all spheres of public administration; high inflation and rising cost of living; demographic transition and youth unemployment;• declining standards of social services; and popular reaction to policies subservient to United States. Politics of repression, neo liberal reforms, Youth bulge, proliferation of social media, along with the requisite funding and training from donors created a unique history that resulted in the overthrow of dictators in a region, which was ruled by autocrats for centuries. Economic factors more compelling in raising public discontent and resentment, which explains to a certain extent that WHY this revolution took place. External environment, i.e., Successful uprising in Tunisia, coupled with use of social media as an organization tool and funding from US and European pro-democracy NGOs explains how this revolution took place.
Keywords: Public and International Affairs; Arab Spring, 2010-; Revolutions -- Egypt.; Protest movements -- Egypt -- History -- 21st century.